DYNAMIC CHANGES OF FOOD PRODUCERS IN BULGARIA - Blagoev, Dimitar; Gatovski, Ilia; Sterev, Nikolay (Acta Scientiarum Polonorum. Oeconomia, 2014)
The food and beverage production in Bulgaria has dramatically changed after the full EU membership in 2007. This change has affected not just the production structure, but also the import and export structure as well as overall production potential of the agri-food sector. The aim of the paper is to look inside the changes from the perspective of the single producer. This means to answer to the question: why has the Bulgarian agri-food production been getting worse? The analyses showed that food industry does not have the ability to move over the 1980s values. Partially this state is a result of misunderstanding by food processors how to manage their production more efficiently. The greatest potential for dynamic change of Bulgarian food industry is in the innovation inputs (development of new products and technologies improvement overall marketing). For food sector the major role, among all types of innovations, is played by product innovations.